The Politics of Taxes for Health: An Analysis of the Passage of the Sugar-Sweetened Beverage Tax in Mexico - Erin James; Martín Lajous; Michael R. Reich (Taylor & Francis Group, 2020)
This article explores the politics of passage of the sugar-sweetened beverage (SSB) tax in Mexico, using published documents, media articles, and interviews with key stakeholders. The article examines first the period of agenda setting when the tax was included in the President's fiscal reform package; and second, the period of legislative passage, when the bill was introduced in Congress and was passed. The analysis uses Kingdon's three streams theory of agenda setting, to explain how the tax emerged on the agenda and how agenda setting shaped and enabled legislative passage. The article offers five lessons related to the politics of passing the SSB tax in Mexico. First, passing an SSB tax was difficult and required high-level organization, cooperation, planning, and effort. Second, supporters needed an understanding of how to manage the political and economic context, facilitated by a grant from Bloomberg Philanthropies. Third, framing the tax as generating revenue helped get the proposal onto the policy agenda and enabled buy-in from the powerful Ministry of Finance (Hacienda). Fourth, forming networks within the legislature early on allowed tax proponents to have a network of allies within Congress ready when the SSB tax was introduced as a bill. Finally, early public relations campaigns helped shape public perception that Mexico's obesity epidemic was driven in part by SSB consumption. This is the first paper that uses political science theory and primary data collection and interviews with a broad range of stakeholders, to explain how Mexico passed an SSB tax despite opposition from a strong national SSB industry.